Formation Of Students' Academic Character Through The Research Methodology Course In Renewable Energy Engineering Students Of Akom (Olat Maras Community Academy) - Hidayati, Sri Wahyu; Utama, Abdul Alimun (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The development of students’ academic character is a crucial objective in higher education, particularly through courses that emphasize scientific processes. The Research Methodology course plays a strategic role in fostering academic character values such as scientific integrity, responsibility, perseverance, and critical thinking. This study aims to examine the role of the Research Methodology course in shaping the academic character of Renewable Energy Engineering students at the Olat Maras Community Academy (AKOM). This study employs a literature review method, utilizing data sources from books, nationally accredited journals, and relevant academic documents. Data were collected through systematic literature searches and analyzed using descriptive qualitative analysis. The findings indicate that research methodology learning integrated with library literacy effectively strengthens students’ academic character through the cultivation of academic ethics, the use of credible scholarly sources, and the development of critical thinking skills in reviewing theories and previous studies. These results confirm that the Research Methodology course functions not only as a means of developing research skills but also as an essential medium for fostering students’ academic character, particularly in the field of renewable energy engineering.